Relationship Host Behavior and The Environment of DHF Incidence in Wonokusumo Surabaya - Sofa Nutrima Rismawati; Ira Nurmala (Universitas Airlangga, 2018)
ABSTRACT Free Number of larvae (ABJ) in RW 15, Wonokusumo Village is 85%. However, the incidence of Dengue Hemorrhagic Fever (DHF) is still high, ie 17 cases. The high incidence rate of DHF is due to the interaction between host, agent and environment. Host in terms of behavior, dengue virus as an agent and environment derived from the surrounding conditions that can cause and trigger the spread of DHF. The purpose of this research is to analyze the relationship of host and environment behavior to the occurrence of DHF in RW 15. This research using cross sectional design. Random sampling using the guy method. How to calculate the method guy is 10% of the population so that obtained a sample of 78 respondents. Primary data collection technique is done through indepth interview and filling questionnaire. Secondary data collection was obtained from Wonokusumo Puskemas report and report from Surabaya City Health Office. The research was conducted in RW 15. The result of bivariate statistic test showed significant relation between knowledge, attitude, action and environment against DHF incidence with p> α, 0,00> 0,05. The conclusion of this research is that there is host and environment interaction to DHF incidence. Suggestion of this research is procurement of work program every month, independent larvae monitoring movement by society and 3M movement plus every week on Thursday and procurement of training of cadre jumantik about how and regulation of dosage of abate powder according to dose. Keywords: host behavior, environment, disease Dengue Hemorrhagic Fever